Penggunaan Media Flipchart untuk Meningkatkan Hasil Belajar Tematik - Irda Nelly; Sri Erdawati (Jurnal Pendidikan dan Kewarganegara Indonesia, 2024)
The use of learning media can increase enthusiasm and make it easier for students to understand the material, so that students can obtain good learning results. However, there are still teachers who rarely use media and only use textbooks and blackboards. This makes students less interested in paying attention to learning and student learning outcomes become low. The aim of this research is to determine the increase in thematic learning outcomes by using flipchart media for class III students at SDN 010 Sungai Beringin. This type of research is Classroom Action Research (PTK). This research was carried out in two cycles, where each cycle consisted of 3 meetings with 4 stages, namely, planning, implementation, observation and reflection. The subjects in this research were class teachers and class III students at SDN 010 Sungai Beringin. The data in this research was collected using observation techniques, tests, field notes and documentation. In this research, to analyze the data using the presentation formula. From the results of the analysis it can be concluded that in the pre-cycle student learning outcomes reached a percentage of 43%, including in the "fairly good" category. After implementing the use of flipchart media in cycle I, the completion percentage was 64%, which was included in the "fairly good" category. The results of observations in cycle II reached a completion percentage of 92%, including in the "Very good" category. So, student learning outcomes can be improved through the use of flipchart media for class III students at SDN 010 Sungai Beringin.